A cultural system to reduce weed interference in organic soybean. Issue 4 (25th April 2014) - Anderson, Randy L.
Abstract: Organic producers are seeking alternative tactics for weed control, so that they can reduce their need for tillage. In this study, we examined cultural strategies for controlling weeds during the transition from a cool-season crop to soybean. The study was arranged as a two-way factorial, with factors being choice of cool-season crop and tillage treatments. The cool-season crops were either spring wheat harvested for grain or an oat–pea mixture harvested for forage. Five tillage treatments, ranging from intensive tillage to no-till, were established following each cool-season crop. Two tillage treatments included the cover crops, oat plus oilseed radish. Soybean was planted the following growing season. Each soybean plot was split into two subplots: weed-free and weed-infested. A cultural system comprising oat/pea as a preceding crop with no-till and cover crops reduced weed biomass in soybean 63% compared to intensive tillage. Reduced weed biomass resulted because of delayed weed emergence and lower weed community density. Consequently, soybean yielded 14% more in this treatment than with the intensive tillage treatment when weeds were present. Weed community composition also differed between the two systems; horseweed and field dandelion were prominent in no-till, whereas common lambsquarters, redroot pigweed and buffalobur were prevalent in the tillage control. Other treatments did not control weeds better than intensive tillage. A cultural system approach may minimize the need for tillage during the interval between cool-season crops and soybean.